Biomarkers and Pharmacogenetics in Pancreatic Cancer - Xu, Xunhai; Strimpakos, Alexios S; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Appropriate identification and validation of biomarkers as well as pharmacogenetics are important in formulating patient-oriented, individualized chemotherapy or biological therapy in cancer patients. These markers can be especially valuable in pancreatic cancer, where high mortality and complex disease biology are frequently encountered. Recently, several advances have been made to further our knowledge in this specific area of pancreatic cancer. In the 2011 American Society of Clinical Oncology (ASCO) Annual Meeting, researchers have presented several interesting results in biomarkers development: the identifications of 9 single nucleotide polymorphisms (SNPs) that is associated with positive efficacy of gemcitabine (Abstract #4022); the introduction of circulating tumor cells as a prognostic markers in pancreatic adenocarcinoma (Abstract #e14657); the re-affirmation of plasma cytidine deaminase (CDA) as a positive predictive markers for gemcitabine efficacy, as well as the postulations that CDA*3 as a potential genotype marker to predict gemcitabine responses (Abstract #e14645); and finally the retrospective tumor tissues analysis in the Arbeitsgemeinschaft Internistische Onkologie (AIO) trial in an attempt for epidermal growth factor receptor (EGFR) pathway biomarker identifications (Abstract #4047). Image: Circulating tumor cells and process of metastasis (Detail. Copyright ©2002 from Molecular Biology of the Cell by Alberts et al. New York, NY, USA: Garland Sciences, 2002:132.